Estudo do comportamento termomecânico e análise da formação de orientações preferenciais de aços com 6,5% Si conformados por spray - Bonon, Felipe Rehder (2012)
Termomechanical behavior of spray formed 6.5% Si-Carbon steels were analyzed by physical simulation, through torsion tests, and the evolution of preferential orientation were analyzed in order to electrical devices. Low carbon steel was used in spray forming, and the parameters were changed in order to minimize porosity. The carbon content in Specimens influence in hot mechanical behavior were analyzed in torsion tests in only one pass until fracture, in warm temperatures ranging from 700 °C to 930 °C in a specific strain rate of 1s-1. Microstructure evolution was analyzed in SEM (scanning electron microscope) and the texture through EDSD (electron backscatter diffraction). Results shows that alloy ductility are improved with the carbon contents and process used, temperature and strain rate, and in some processes conditions preferential orientation necessary in electrical devices is obtained.